2009
DOI: 10.1002/pmic.200800696
|View full text |Cite
|
Sign up to set email alerts
|

2‐D DIGE analysis of Senegalese sole (Solea senegalensis) testis proteome in wild‐caught and hormone‐treated F1 fish

Abstract: In the farmed flatfish Senegalese sole, F1 males reared in captivity often show lower sperm production and fertilization capacity than wild-caught males. To gain insights into the molecular mechanisms that may be altered in the F1 testis, we used 2-D DIGE to compare the protein profiling of the testis of wild-caught males at the spermiation stage with that of F1 males showing different stages of germ cell development after hormone treatment in vivo. The abundance of 58 out of 1014 protein spots was found to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Riba 2004;Costa et al 2009a, b;Oliva et al 2010). In addition, some successful attempts using ''omic'' approaches can already been found, although most also relate to aquaculture, such as transcription analysis by cDNA microarrays and PCR techniques (Manchado et al 2008;Osuna-Jiménez et al 2009;Prieto-Á lamo et al 2009 and a few others) and proteomics (Forné et al 2009;Salas-Leiton et al 2009;Costa et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Riba 2004;Costa et al 2009a, b;Oliva et al 2010). In addition, some successful attempts using ''omic'' approaches can already been found, although most also relate to aquaculture, such as transcription analysis by cDNA microarrays and PCR techniques (Manchado et al 2008;Osuna-Jiménez et al 2009;Prieto-Á lamo et al 2009 and a few others) and proteomics (Forné et al 2009;Salas-Leiton et al 2009;Costa et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Much research has been performed on this species in the areas of aquaculture, marine ecology and ecotoxicology. ''Omics'' (proteomics and transcriptomics) techniques have, inclusively, been performed on Senegalese soles, although more for aquaculture-than for ecotoxicology-related studies (e.g., Forné et al 2009Forné et al , 2011Salas-Leiton et al 2009;Osuna-Jiménez et al 2009;Costa et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…This species also shows highly asynchronous spermatogenesis since once males reach sexual maturity spermatogenic activity and spermiogenesis are maintained almost all year-round, although spermiation is slightly enhanced during the annual fluctuation of female ovulation (García-Ló pez et al 2006a,b). Recent studies of sole have revealed a complex cell-type-specific and stage-specific pattern of gene expression during spermatogenesis, and that human chorionic gonadotropin (hCG) can regulate the expression of genes potentially involved in steroidogenesis, progression of spermatogenesis and germ cell maturation (Cerdà et al 2008, Forné et al 2009, Mechaly et al 2012. However, the specific actions of Fsh and Lh on gene expression during spermatogenesis in Senegalese sole remain unknown.…”
Section: Introductionmentioning
confidence: 99%